Elastosonographic Evaluation of Endometrium in Postmenopausal Bleeding - İsmail Burak Gültekin; Orhan Altınboğa; Serap Gültekin; Elif Akkaş Yılmaz; Gökşen İnanç İmamoğlu; Afra Alkan; Tuncay Küçüközkan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of this study was to evaluate the elastosonographic changes of endometrium in postmenopausal women with uterine bleeding.